Intermanual transfer and bilateral cortical plasticity is maintained in older adults after skilled motor training with simple and complex tasks - Dickins, Daina S. E.; Sale, Martin V.; Kamke, Marc R. (Frontiers in Aging Neuroscience, 2015)
Intermanual transfer refers to the phenomenon whereby unilateral motor training induces performance gains in both the trained limb and in the opposite, untrained limb. Evidence indicates that intermanual transfer is attenuated in older adults following training on a simple ballistic movement task, but not after training on a complex task. This study investigated whether differences in plasticity in bilateral motor cortices underlie these differential intermanual transfer effects in older adults. Twenty young (<35 years old) and elderly adults (>65 years) trained on a simple (repeated ballistic thumb abduction) and complex (sequential finger-thumb opposition) task in separate sessions. Behavioral performance was used to quantify intermanual transfer between the dominant (trained) and non-dominant (untrained) hands. The amplitude of motor-evoked potentials (MEPs) induced by single pulse transcranial magnetic stimulation (TMS) was used to investigate excitability changes in bilateral motor cortices. Contrary to predictions, both age groups exhibited performance improvements in both hands after unilateral skilled motor training with simple and complex tasks. These performance gains were accompanied by bilateral increases in cortical excitability in both groups for the simple but not the complex task. The findings suggest that advancing age does not necessarily influence the capacity for intermanual transfer after training with the dominant hand.